Efeitos do pneumoperitônio com CO2 sobre a pressão intra-ocular (PIO) e parâmetros cardiorrespiratórios em cadelas submetidas à ovariohisterectomia laparoscópica - Corrêa, Luis Felipe Dutra (2016)
Videolaparoscopic procedures are increasingly gaining ground in the routine of veterinary medicine. In this context, important research projects involving the use of pneumoperitoneum with CO2 and its correlation with possible changes in intraocular pressure (IOP) become more important. This thesis presents a bibliographical survey to contextualize the subject, showing the factors that may influence the IOP (Article 1) and also to verify the influence of three different speeds of pneumoperitoneum with the constant inflation pressure (12 mmHg) and the influence on the cardiorespiratory variables in animals submitted to ovariohysterectomy (OVH) - (Article 2). For the experimental stage, 40 female patients, with an average age of 5 ± 2 months, were selected through clinical, haematological and ophthalmologic examination. Afterwards, they were randomly distributed into four groups, with ten animals each. In G1, the animals were submitted to the videolaparoscopic procedure with inflation rates of 1 l / min; The G2, with a speed of 1.5 l / min and G3, 2 L / min. G4 was called the control group and conventional OVH was performed. The analyzed variables were HR, RR, SAP, DAP, MAP, CVP, ETCO2, SAT and IOP. Patients were evaluated preoperatively (M0) and monitored up to 2 hours after surgery (M1 to M10). The cardiorespiratory variables studied were altered with the presence of pneumoperitoneum, being significant before and after the presence of carbon dioxide (p≤0.005). The effect of between groups was not statistically significant (p> 0.005), and the changes were related to the presence of pneumoperitoneum and the rate of insufflation. The ocular pressures had their increase associated with the pneumoperitoneum and not to the rate of insufflation, as their values stayed within the physiological limits.It was concluded that healthy animals, although they have their intraocular pressure stable when submitted to the pneumoperitoneum with CO2 at the speeds and pressure studied, suffer IOP increase within the physiological patterns after insufflation.